PM module for management of pod borer complex in pigeonpea (Cajanus cajan) - Rajabaskar, D; Natarajan, N (Indian Journal of Plant Protection, 2020)
Field experiments were conducted during Kharif 2014, 2015, 2016 to validate IPM module for podborer complex in pigeonpea (Cajanus cajan) and compared with Non IPM (farmers’ practices). The IPM module included, pigeonpea intercropped with mungbean at 4:2 ratio in a ridges and furrow system, sprayed neem oil soap 1% concentration at the vegetative stage, installed Helicoverpa pheromone trap @ 12/ha, and two spray of new insecticide molecule Flubendiamide @ 125ml/ha at the time of 50 per cent flowering stage and Chlorantraniliprole 18.5SC @ 30g ai/ha at 15 days later. The Non IPM practices included, spraying of Monocrotophos 36 WSC @ 1250ml/ha twice at peak flowering and pod initiation stages. The incidences of H. armigera eggs (p=0.02), larvae (p=0.003) and per cent damage (p=0.03), Maruca webbings (p=0.04) and pod fly infestation (p=001) were low in IPM plot and found statistically significant compared to Non IPM plot. The cumulative yield of pigeonpea for three years was 800kg/ha whereas in Non IPM plot the yield was 320kg/ha. The intercrop besides serving as host for natural enemies it gave an additional income and it boosted the net return from IPM plot and average benefit cost over Non IPM practices was 1:3.7.